2013
DOI: 10.11646/zootaxa.3663.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots of new species discovery: new mite species described during 2007 to 2012

Abstract: (991 speciesThe top family is the Eriophyidae, which alone accounted for nearly 15% of the total new species. Geographically, the new species were described from 92 countries and their distribution among these countries is highly uneven. The top 10 countries accounted for 62% of all the new species and the top country, China, alone accounted for 18% of the total. The average number of new species per country is 15 and no more than a fifth of the countries are above the average, and 40% of the countries have on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 427 publications
1
25
0
Order By: Relevance
“…Overall, the average number of new species per year increased from 51 during 2007-2012 to 80 during 2013-2015. This is similar to the trend in the Trombidiformes (an increase from 132 during 2007-2012to 163 during 2013Liu & Zhang 2016) but different from that in the Parasitiformes (a decrease from 57 during 2007-2012to 47 during 2013Lam & Zhang 2016). .…”
Section: Trends In the Number Of New Speciessupporting
confidence: 80%
See 1 more Smart Citation
“…Overall, the average number of new species per year increased from 51 during 2007-2012 to 80 during 2013-2015. This is similar to the trend in the Trombidiformes (an increase from 132 during 2007-2012to 163 during 2013Liu & Zhang 2016) but different from that in the Parasitiformes (a decrease from 57 during 2007-2012to 47 during 2013Lam & Zhang 2016). .…”
Section: Trends In the Number Of New Speciessupporting
confidence: 80%
“…At the infraorder level within the Sarcoptiformes, over 73% of the 242 new species described in the two journals during are in Desmonomata (versus 80.58% during 2007-2012 Tables 2, 3). At the family level, the distribution of new species among 50 families is highly uneven; most of these new species (62%) are from the top 10 families (two families shared the rank 10 so there are 11 families in top 10 ( Table 3).…”
Section: Taxonomic Distribution Of New Speciesmentioning
confidence: 99%
“…A recent survey of new mite species described during six years (2007)(2008)(2009)(2010)(2011)(2012) showed that the distribution of 1379 new species are highly unevenly distributed among 92 countries, with the top 10 countries accounting for 62% of the total (Liu et al 2013). This paper is a follow-up of Liu et al (2013) and provides a survey of new species of the Trombidiformes described during the last three years (2013)(2014)(2015). The methods of Liu et al (2013) are followed here and the patterns of distribution of new species of the order Trombidiformes described during 2013-2015 are summarised.…”
Section: Introductionmentioning
confidence: 99%
“…This paper is a follow-up of Liu et al (2013) and provides a survey of new species of the Trombidiformes described during the last three years (2013)(2014)(2015). The methods of Liu et al (2013) are followed here and the patterns of distribution of new species of the order Trombidiformes described during 2013-2015 are summarised. The bulk of this paper presents a list of the type localities and depositories of all new species of the Trombidiformes published in Zootaxa and Systematic & Applied Acarology (SAA) during the last three years (2013)(2014)(2015) with the main purpose of exposing newly described species to a wider community as similar papers in the past (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, the genus Acaralox currently includes two described species: Acaralox arundinaceus Skoracka and Acaralox croatiae Skoracka, Labrzycka et Rector (Skoracka 2002, Skoracka et al 2009). In the Hungarian fauna no Acaralox species have been reported so far (Ripka 2007(Ripka , 2008, and no Acaralox species have hitherto been found on common vervain (Verbena officinalis) in the world (Amrine & Stasny 1994, 1996, Davis et al 1982, Liu et al 2013. Just an other species, Aculus verbenae (Keifer) is known from Verbena sp.…”
Section: Introductionmentioning
confidence: 99%